Cationic rhodium(I)/BIPHEP complex-catalyzed cross-cyclotrimerization of silylacetylenes and unsymmetrical electron-deficient internal alkynes. Issue 34 (19th August 2015) - Heya, Arisa; Namba, Tomoya; Hara, Jun; Shibata, Yu; Tanaka, Ken
Graphical abstract: Abstract: It has been established that a cationic rhodium(I)/BIPHEP complex catalyzes the chemo- and regioselective intermolecular cross-cyclotrimerization of silylacetylenes with unsymmetrical electron-deficient internal alkynes. Chemoselectivity was highly dependent on steric bulk of the unsymmetrical electron-deficient internal alkynes used. Two molecules of sterically less demanding alkynoates and alkynone reacted with one molecule of the silylacetylene, on the contrary, one molecule of a sterically demanding alkynoate reacted with two molecules of the silylacetylene.